RETRACTED: Near-cure in patients with Gadolinium deposition disease undergoing intravenous DTPA chelation - Semelka, Richard C.; Ramalho, Miguel (Frontiers in Toxicology, 2024)
PurposeTo demonstrate and evaluate factors contributing to near-cures in patients with Gadolinium Deposition Disease (GDD) undergoing intravenous (IV) DTPA chelation.MethodsPatients who had undergone or are currently undergoing DTPA chelation for GDD were included in this report based on their medical records that showed their perceived improvement was at least 80% back to normal. A survey was developed that included factors commonly reported by patients treated in one clinic to determine if these ‘near-cured’ (pre-MRI baseline health) individuals possessed certain factors and lacked others. The anonymized survey was emailed to these individuals by the principal treating physician, the only investigator not blinded to the subjects. This report describes clinical documentation of patient status and their underlying factors in individuals treated by the primary author, and no research was performed. The survey was sent to sixteen individuals; Fourteen patients completed it (10 females; 41.1 ± 11.2 y/o).ResultsThe most common factor was the administration of ≤5 lifetime doses of a Gadolinium-Based Contrast Agents (GBCA) (12/14). Unconfounded agents triggering GDD were seen in nine subjects. Most subjects (12/14) initiated chelation in the first year after the causative GBCA, and most (11/14) underwent ≤10 chelations with DTPA. Good healthcare status prior to MRI was observed in 5 subjects. The majority (11/14) described their immune status as strong. Severe physical disability prior to chelation was seen in 1.ConclusionSubjects with GDD can experience near-cure with IV DTPA chelation. Factors surveyed that predict near-cure include the start of chelation in the first year, few GBCA administrations, and good health status before MRI with GBCA injection. Nonetheless, a few patients with predictors of less successful outcomes still experienced near-cure.